Analisis Perubahan Motivasi Belajar Siswa Di Tengah Tingginya Penggunaan Smartphone - Zike Farhani; Kamelia Amanda; Lovely Bunga Mellaty; Zulfani Sesmiarni (KOLONI, 2025)
Over the past decade, smartphone use among schoolchildren has increased rapidly and has become a daily activity for students. Without a smartphone for even a day, students seem to become disoriented. These devices are no longer simply used for communication; they have also become a source of entertainment, games, and access to a vast and limitless amount of information. This high level of smartphone use has also led to a decline in students' interest in learning. This study attempts to examine changes in learning motivation through a literature review, reviewing various research findings from both within and outside the country. The findings indicate that excessive smartphone use has a more negative impact on students' intrinsic motivation, concentration levels, and self-discipline. However, smartphones also have a positive side when used appropriately in a learning context, for example through e-learning or educational applications that support learning activities. Overall, this study emphasizes the need for better monitoring of smartphone use and strengthening digital literacy, so that these devices can be used to support the learning process and not hinder it.